The Effectiveness of Crime Analysis for Crime Reduction: Cure or Diagnosis?. (May 2014) - Santos, Rachel Boba
Many researchers and police chiefs have asked the question, "Does crime analysis reduce crime?" This question is a difficult one is because the link between crime analysis and crime reduction is not direct. Just like the use of MRI results does not cure an illness, crime analysis is the process of using examining data and making conclusions; it is not a crime reduction strategy (cure) by itself. The connection between crime analysis and crime reduction is only through an effective police strategy that uses crime analysis. So, instead of evaluating whether crime analysis reduces crime, this article examines the role of crime analysis as a component in specific police crime reduction strategies. The evidence presented is not based on research of effectiveness of crime analysis, since there is none, but on the effectiveness research of police approaches, such as the standard model of policing, community policing, disorder policing, problem-oriented policing, hot spots policing, and the "pulling levers" focused deterrence approach, as well as popular and new approaches, such as Compstat, intelligence-led policing (ILP), and predictive policing, and the level at which crime analysis plays a role in each. Through a qualitative assessment, the author concludes that there is a clear pattern that crime analysis plays a significant role in police approaches that are effective, and just as apparent, crime analysis plays a very limited role in policing approaches that are ineffective. In addition, assessment of the policing approaches that have not been systematically evaluated, but have been widely adopted (i.e., Compstat) or are relatively new (i.e., ILP and predictive policing), reveals that crime analysis plays a central and visible role. This article shows that crime analysis is a key component in successful crime reduction efforts. Because this is a qualitative assessment from a fairly broad perspective, several recommendations are made for future research that will more fully understand the relationship between crime analysis and police effectiveness.